2000
DOI: 10.1007/s004210050072
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen consumption with unloaded walking and load carriage using two different backpack designs

Abstract: The purpose of this study was to assess the energy expenditure associated with load carriage using both a traditional rucksack and a new rucksack design, the AARN rucksack, which incorporates front balance pockets. Nine volunteers walked at 3 km h(-1) at various uphill and downhill gradients on a treadmill without a load and carrying a load of 25.6 kg in each of the rucksacks. The oxygen consumption associated with both of the loading conditions was significantly (P < 0.001) higher than that associated with un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 20 publications
9
53
0
Order By: Relevance
“…This is consistent with previous studies in the area (e.g. Lloyd et al 2000a) The load was calculated based on the body mass at the habituation session and was made up of the mass of the actual carrying device plus appropriate weightlifting plates, (between 2.5 kg and 10 kg), and 100g sandbags, which allowed the load to be adjusted to within 50g of the required load. Each participant attended the laboratory one week later to repeat the experiment with the other loading device.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…This is consistent with previous studies in the area (e.g. Lloyd et al 2000a) The load was calculated based on the body mass at the habituation session and was made up of the mass of the actual carrying device plus appropriate weightlifting plates, (between 2.5 kg and 10 kg), and 100g sandbags, which allowed the load to be adjusted to within 50g of the required load. Each participant attended the laboratory one week later to repeat the experiment with the other loading device.…”
Section: Methodssupporting
confidence: 76%
“…Datta and Ramanathan (1971) and Legg and Mahanty (1985) both compared a range of loading conditions and found small advantages for double pack systems, where the load was carried split between the back and the front of the trunk, over back-loading alone. These findings were supported by Lloyd and Cooke (2000a). Stuempfle et al (2004) reported a significant advantage for loads carried high on the back compared to loads carried in a low position.…”
Section: Introductionmentioning
confidence: 66%
“…Net metabolic ratios calculated from studies of quadrupeds trotting with back loads are also lower than the values from studies of walking quadrupeds, but as with the human studies the fractional increase in metabolic rate is generally slightly Measurements in which the mass ratio was less than 1.5 times the unloaded body mass. Solid circles, five human studies with the load applied in back packs (Soule et al, 1978;Pierrynowski et al, 1981;Duggan and Haisman, 1992;Lloyd and Cooke, 2000;Quesada et al, 2000). Open circles, human data for loads carried in a waist pack (Griffin et al, 2003).…”
Section: (N=6) Energy Cost Of Loaded Walking and Runningmentioning
confidence: 99%
“…Research has shown that placing load closer to the body's CoM results in a reduction in energy cost (Abe et al, 2008;Coombes and Kingswell, 2005;Datta and Ramanathan, 1971;Lloyd and Cooke, 2000b), with a more upright walking posture being adopted (Kinoshita, 1985;Harman et al, 1994). In terms of the kinetic effects a reduced maximum braking force and stance time, while increasing force minimum are reported outcomes as a result of distributing load around the trunk (see references below).…”
Section: Introductionmentioning
confidence: 99%